21st century architecture : apartment living - Browne, Beth. (Australia : Images Publishing, 2011)
Presents new and inspiring apartment interiors in a diverse range of styles designed by leading international architects.
3 Mews dwellings -- 15 Central Park West -- 59th Street penthouse -- Apartment 65 -- Apartment K -- Architect's apartment -- Attico Apartment -- Bell Penthouse -- Beverly Street Condo -- Blur Loft -- Bonanova -- Bondi penthouse -- Breck loft -- Bulleting -- CAP apartment -- Capri apartment -- Carr apartment -- Collector's loft -- Fifth Avenue townhouse -- FILC apartment -- Harbour's edge -- Highpoint Humelegarden apartment -- Kent street apartment -- LC apartment -- Ludwig penthouse -- Manhattan apartment -- The mansion on Peachtree -- Maria Borges apartment -- Melbourne apartment -- Milsons point -- Mini loft -- New York apartment -- Norman Reach penthouse -- One Rincon hill -- Organic space -- Pacific heights apartment -- Parks residence -- Playroom apartment -- Pyrmont -- Quant 1 -- Riverside drive -- Rosas apartment -- S -- The SCH -- Seafront apartment -- SF apartment -- Shuwai -- Spring Street apartment -- St. Louis art house -- St. Ursula Street apartment -- Transparent loft -- TriBeCa loft -- Urban condominium -- Index of Architects.
Includes index.
Keywords: APARTMENTS -- DESIGN AND CONSTRUCTION -- PICTORIAL WORKS